2006
DOI: 10.1007/s00120-006-1052-4
|View full text |Cite
|
Sign up to set email alerts
|

Testikulärer Keimzelltumor und Sarkoidose

Abstract: Several case reports and small case series have described a total of 66 patients with sarcoidosis and testicular cancer so far. This report describes three additional cases. We highlight the association of sarcoidosis and testicular cancer and comment on the potential impact of this connection on the interpretation of the radiological and pathological findings in suspected cancer relapse. Sarcoidosis, a condition that can be combined with testicular cancer, should always be considered in the differential diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…[74] Rayson et al . [75] reported that the sarcoidosis incidence among patients with testicular cancer was >6/10,000 or approximately 100 times the baseline incidence expected for young white males.…”
Section: Scrotum Testicular and Paratesticular Structuresmentioning
confidence: 99%
“…[74] Rayson et al . [75] reported that the sarcoidosis incidence among patients with testicular cancer was >6/10,000 or approximately 100 times the baseline incidence expected for young white males.…”
Section: Scrotum Testicular and Paratesticular Structuresmentioning
confidence: 99%
“…When we search through the sarcoidosis-malignancy association in the literature, sarcoidosis plays the most frequent association with HL among haematopoietic malignancies and with germ cell tumours among non-haematopoietic malignancies [5,6]. This predilection endows a critical role to specific tumour antigens in the pathogenesis of sarcoidosis, suggesting that HL and seminoma antigens are more 'sarcoidogenic' than others.…”
Section: Discussionmentioning
confidence: 99%
“…Later on, in 1986 Brinker described the sarcoidlymphoma syndrome, which is defined as a lymphoma appearing at least 1 or 2 years after a diagnosis of sarcoidosis [3]. Then, he studied more specifically the association between granulomatous reactions and cancers [2].It seems that these reactions are found in 5% of neoplastic diseases [4], and the association is particularly strong with germinal testicular cancer [5], Hodgkin disease and certain T-cell lymphomas [6].…”
Section: Introductionmentioning
confidence: 99%